2014
DOI: 10.1186/s12883-014-0181-4
|View full text |Cite
|
Sign up to set email alerts
|

Dependency-like behaviors and pain coping styles in subjects with chronic migraine and medication overuse: results from a 1-year follow-up study

Abstract: BackgroundEven after successful detoxification, 20-40% of subjects presenting chronic migraine with symptomatic medication overuse (CMwMO) relapse into medication overuse within one year. In this restrospective analysis on subjects referred to our center for detoxification, we investigated whether personality traits, dependency-like behaviors and pain coping styles predicted those who relapsed into medication overuse within the 12 months following the detoxification and those who did not.Methods63 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…This allowed them to seek help and maintain an optimistic outlook as to outcome. Previous research showed that patients with longer duration of CM had lower rates of internal control over pain and higher rates of attribution to external factors , and that increases in perceptions of internal control over pain (ie, being aware of individual responsibilities in chronification and of the importance of chance) were associated with successful withdrawal …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed them to seek help and maintain an optimistic outlook as to outcome. Previous research showed that patients with longer duration of CM had lower rates of internal control over pain and higher rates of attribution to external factors , and that increases in perceptions of internal control over pain (ie, being aware of individual responsibilities in chronification and of the importance of chance) were associated with successful withdrawal …”
Section: Discussionmentioning
confidence: 99%
“…Withdrawal is considered effective when a reduction of 50% in headache frequency is confirmed at 12 months, and research findings show an effectiveness of withdrawal up to 5 years after discharge . However, it is common clinical experience that some patients are more prone to relapse into MOH and to need further treatment after a shorter period than others, with 1‐year relapse rates found to be between 20.5 and 41% . The predictors of short‐term relapse include: high frequency of migraine attacks, recent history of withdrawal treatment, emergency room admission after withdrawal, high‐depression scores, residual symptomatology after withdrawal treatment and a greater number of previously tried preventive treatments, type of primary headache and type of overused medication, and a genetic predisposition for success of detoxification therapy and 12‐month relapse was also shown .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is a common clinical practice experience that some patients seem to be more prone to fall again into MO and, thus, to be in need of further withdrawal treatment within a short‐term period. Few studies specifically addressed relapse rates: they showed that one‐year relapse rate ranged between 20.5% and 41%, and increased up to 45% by four years . In those studies that addressed 12‐months relapse, a total of 384 patients were included, and 126 relapsed, thus showing an average relapse rate of 32.8%.…”
Section: Introductionmentioning
confidence: 99%
“…In those studies that addressed 12‐months relapse, a total of 384 patients were included, and 126 relapsed, thus showing an average relapse rate of 32.8%. Predictor of relapse included: high‐frequency migraine (ie, >8 days/month), a lower reduction of headaches frequency after withdrawal treatment and a greater number of previously tried preventive treatments; type of primary headache and of overused medication, with migraineurs and in general patients overusing triptans having lower relapse rates; residual symptomatology; being on medical therapy only (compared to adjuvant behavioral technique) . A genetic predisposition, involving genetic variants of the catechol O‐methyltransferase and SLC6A4 genes, was also found .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation